ENHANCING EFL STUDENTS’ RECOGNIZING ASSUMPTION SKILL THROUGH PROBLEM-BASED LEARNING IN INDONESIAN HIGH SCHOOLS - Sumartono; Sri Wuli Fitriati; Sri Wahyuni; Zulfa Sakhiyya (University of Kuningan, 2026)
Education plays a pivotal role in fostering higher-order thinking skills that enable learners to navigate complex social and epistemic realities. Within the Indonesian educational reform agenda particularly the Merdeka Belajar (Freedom to Learn) curriculum there has been an explicit shift from teacher-centered to student-centered pedagogies that promote inquiry, reasoning, and learner autonomy. This study investigates the impact of Problem-Based Learning (PBL) on students’ assumption recognition skills, a critical subcomponent of higher-order thinking essential for argument evaluation and reflective judgment in English language learning. Employing a quasi-experimental design, the research involved senior high school students in Brebes Regency who were divided into experimental and control groups. The experimental group received PBL instruction enriched with scaffolds for identifying and questioning assumptions, while the control group engaged in conventional teacher-led learning. Quantitative data were collected through the Assumption Recognition Subscale of the Watson–Glaser Critical Thinking Appraisal and analyzed using inferential statistics, complemented by qualitative classroom observations to examine facilitation dynamics and discourse patterns. Results revealed that the PBL group demonstrated statistically significant improvements in assumption recognition compared to the control group, indicating that structured inquiry and collaborative reasoning effectively enhance critical subskills. Qualitative findings further suggested that teacher facilitation, peer dialogue, and problem authenticity were key mediators of cognitive engagement. These results highlight the potential of PBL as a pedagogical model that operationalizes the Merdeka Curriculum’s vision of student-centered learning by cultivating reflective, autonomous, and epistemically responsible learners. The study concludes with pedagogical implications for teacher education, curriculum design, and assessment practices aimed at strengthening critical thinking in English language classrooms.